Dark Energy Survey Year 3 Results: Galaxy mock catalogs for BAO analysis - Ferrero, I.; Crocce, M.; Tutusaus, I.; Porredon, A.; Blot, L.; Fosalba, P.; Carnero Rosell, A.; Avila, S.; Izard, A.; Elvin-Poole, J.; Chan, K. C.; Camacho, H. [UNESP]; et al. (EDP Sciences, 2021)
The calibration and validation of scientific analysis in simulations is a fundamental tool to ensure unbiased and robust results in observational cosmology. In particular, mock galaxy catalogs are a crucial resource to achieve these goals in the measurement of baryon acoustic oscillation (BAO) in the clustering of galaxies. Here we present a set of 1952 galaxy mock catalogs designed to mimic the Dark Energy Survey Year 3 BAO sample over its full photometric redshift range 0:6 < zphoto < 1:1. The mocks are based upon 488 ICE-COLA fast N-body simulations of full-sky light cones and were created by populating halos with galaxies, using a hybrid halo occupation distribution halo abundance matching model. This model has ten free parameters, which were determined, for the first time, using an automatic likelihood minimization procedure.We also introduced a novel technique to assign photometric redshift for simulated galaxies, following a two-dimensional probability distribution with VIMOS Public Extragalactic Redshift Survey data. The calibration was designed to match the observed abundance of galaxies as a function of photometric redshift, the distribution of photometric redshift errors, and the clustering amplitude on scales smaller than those used for BAO measurements. An exhaustive analysis was done to ensure that the mocks reproduce the input properties. Finally, mocks were tested by comparing the angular correlation function w(θ), angular power spectrum ζp(rΓ) and projected clustering p(r?) to theoretical predictions and data. The impact of volume replication in the estimate of the covariance is also investigated. The success in accurately reproducing the photometric redshift uncertainties and the galaxy clustering as a function of redshift render this mock creation pipeline as a benchmark for future analyses of photometric galaxy surveys.
Keywords: Catalogs; Galaxies: distances and redshifts; Galaxy: halo; Large-scale structure of Universe; Methods: numerical